The Sw-5 Gene Cluster: Tomato Breeding and Research Toward Orthotospovirus Disease Control - de Oliveira, Athos S.; Boiteux, Leonardo S.; Kormelink, Richard; Resende, Renato O. (Frontiers in Plant Science, 2018)
The Sw-5 gene cluster encodes protein receptors that are potentially able to recognize microbial products and activate signalling pathways that lead to plant cell immunity. Although there are several Sw-5 homologs in the tomato genome, only one of them, named Sw-5b, has been extensively studied due to its functionality against a wide range of orthotospoviruses. The Sw-5b gene is a dominant resistance gene originally from a wild Peruvian tomato that has been used in tomato breeding programs aiming to develop cultivars with resistance against (thrips-transmitted) orthotospoviruses. Here we provide an overview starting from the first reports of Sw-5 resistance, positional cloning and the sequencing of the Sw-5 gene cluster from resistant tomatoes and the validation of Sw-5b as the functional protein that triggers resistance against orthotospoviruses. Moreover, molecular details of this plant-virus interaction are also described, especially concerning the roles of Sw-5b domains in the sensing of orthotospoviruses and in the signalling cascade leading to resistance and hypersensitive response.